Stable Multiwavelength Erbium-Doped Random Fiber Laser - Saleh S.; Cholan N.A.; Sulaiman A.H.; Mahdi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Brillouin scattering; Erbium; Feedback; Fiber lasers; Fibers; Four wave mixing; Laser excitation; Nonlinear optics; Optical fibers; Rayleigh scattering; Ring lasers; Single mode fibers; Erbium doped fiber laser; Laser feedback; Laser stability; Multiwavelength erbium-doped fiber lasers; Power lasers; Pump laser; Random fibers; Pumping (laser)